A survey of outcomes and management of patients post fragility fractures in China. Issue 11 (November 2015) - Wang, O.; Hu, Y.; Gong, S.; Xue, Q.; Deng, Z.; Wang, L.; Liu, H.; Tang, H.; Guo, X.; Chen, J.; Jia, X.; Xu, Y.; et al.
Abstract Summary We found that the fragility hip and vertebral fractures caused excess mortality rates in this Chinese female population, which was unexpectedly lower than those in western countries and other Asian countries. This was the first nationwide survey relating to post-fracture outcomes conducted among Chinese population in Mainland China. Introduction This study aimed to investigate the mortality, self-care ability, diagnosis, and medication treatment of osteoporosis following fragility hip and vertebral fractures through a nationwide survey among female patients aged over 50 in Mainland China. Methods This was a multicenter, retrospective cohort study based on medical chart review and patient questionnaire. Female patients aged 50 or older admitted for low-trauma hip or vertebral fractures and discharged from Jan 1, 2008 to Dec 31, 2012 were followed. Results Total of 1151 subjects of hip fracture and 842 subjects of vertebral fracture were included. The mean age was 73.4 ± 10.0, and the median of duration from index fracture to interview was 2.6 years. The overall 1-year, 2-year, 3-year, 4-year, and 5-year cumulative mortality rates were 3.5, 7.0, 11.2, 13.1, and 16.9 %, respectively. The first year mortality rates in hip (3.8 %, 95% CI 3.3–4.4 %) and vertebral fracture (3.1 %, 95% CI 2.5–3.7 %) were significantly higher than that in the general population (1.6 %). Impaired self-care ability was observed in 33.2, 40.6, and 23.8 % of overall, hip fracture, and vertebral fracture group, respectively. The overall diagnosis rate of osteoporosis was 56.8 %, and bone mineral density (BMD) measurement had never been conducted in 42.0 % among these women. After the index fracture, 69.6 % of them received supplements and/or anti-osteoporotic medications, among which 39.6 % only received calcium with/without vitamin D supplementation. Conclusions The osteoporotic hip and vertebral fractures caused excess mortality rates in this population of Mainland China. The current diagnosis and medical treatment following the fragility fractures is still insufficient in Mainland China.